2018
DOI: 10.31768/2312-8852.2018.40(1):42-47
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Features of Doxorubicin-Resistant Walker 256 Carcinosarcoma and Response of Mast Cells

Abstract: Background: The mechanisms of drug resistance of cancer have not been yet elucidated in details. Recently, the role of mast cells (MCs) in the development of drug resistance has been brought in the limelight. The aim of the study was to examine the morphological features of doxorubicin (DOX)-resistant Walker 256 carcinosarcoma and to assess the response of MCs and histamine content in these cells in relation to the development of resistance to DOX as well as in DOX-resistant tumors. Materials and Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…DOX + EMF treatment caused both necrosis and apoptosis of tumor cells. The development of fibrotic tissue accompanied tumor adaptation to DOX chemotherapy (Boroday and Chekhun 2018) and tissue replacement (Lushnikova et al 2011). These results are consistent with previous investigations, which showed that the mechanism of tumor and liver cell death under the influence of EMF was apoptosis (Alves de Souza et al 2017;Ghodbane et al 2015;Lai 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…DOX + EMF treatment caused both necrosis and apoptosis of tumor cells. The development of fibrotic tissue accompanied tumor adaptation to DOX chemotherapy (Boroday and Chekhun 2018) and tissue replacement (Lushnikova et al 2011). These results are consistent with previous investigations, which showed that the mechanism of tumor and liver cell death under the influence of EMF was apoptosis (Alves de Souza et al 2017;Ghodbane et al 2015;Lai 2019).…”
Section: Discussionsupporting
confidence: 91%
“…H&E stained tissue slides were examined under a light microscope (Olympus BX-41, Olympus Europe GmbH, Japan) according to (Thoolen et al 2010). The assessment of changes in tumor and liver tissues was performed using the histological criteria defined by (Boroday and Chekhun 2018).…”
Section: Histological Evaluationmentioning
confidence: 99%